1969
DOI: 10.1161/01.res.25.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurements of Radii and Wall Thickness of Microvessels in the Anesthetized Rat

Abstract: The purpose of this investigation was to measure the radius and wall thickness of small blood vessels in mesentery and striated (cremaster) muscle in the anesthestized rat. Using the method of image-splitting, the vessel images were sheared at magnifications of 3,OOOx and 6,500x on the video screen. In the resting state, the mean lumen values for the thinnest portion of endothelial capillary were 4.1 ± 1.2µ (SD) in cremaster and 5.6 ± 1.3µ (SD) in mesentery. Lumen and total diameter were also greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 0 publications
0
44
0
Order By: Relevance
“…Reversal of blood-induced large vessel spasm has been reported in vivo, using alpha blockade. 9 ' 20 In vivo studies on the microcirculation have shown that alpha adrenergic stimulation with norepinephrine in higher doses than required to activate vessels elsewhere in the body 51 produced only a moderate vasoconstrictor effect in pial vessels. 38 -"• 48 These results, however, are not consistently reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…Reversal of blood-induced large vessel spasm has been reported in vivo, using alpha blockade. 9 ' 20 In vivo studies on the microcirculation have shown that alpha adrenergic stimulation with norepinephrine in higher doses than required to activate vessels elsewhere in the body 51 produced only a moderate vasoconstrictor effect in pial vessels. 38 -"• 48 These results, however, are not consistently reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…The leukocyte parameters were examined as previously described (2,20,43). Briefly, mice were anesthetized with an intraperitoneal injection of 40 mg of sodium pentobarbital kg Ϫ1 .…”
Section: Methodsmentioning
confidence: 99%
“…Images were recorded on a video recorder with a ϫ40 long-distance objective with a 0.65 numerical aperture. An image-splitting micrometer was adjusted to the phototube of the microscope as described by Baez (2). The image splitter sheared the optical image into two separate images and displaced one with respect to the other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By rotating the image splitter in the phototube, the shearing was maintained at the right angles to the long axis of the vessel. The displacement of one image from the other permitted measurement of the vessel diameter (Baez, 1969). A terminal arteriole and the venule paired with it were selected for study, and any changes in vessel diameter were estimated after the topical application of histamine (2.7 nmol), bradykinin (30 pmol), PAF (39 pmol), sodium nitroprusside (38 nmol), and acetylcholine (17 nmol).…”
Section: Methodsmentioning
confidence: 99%